0 like 0 dislike
0 like 0 dislike
my answer and option different

3 Answers

0 like 0 dislike
0 like 0 dislike
If you were so kind to show us your answer, work, and the options we will give you better help :)
0 like 0 dislike
0 like 0 dislike
f(g(x)) = 3(x^(3)+5)-2 = 3x^(3)+13

f(g(x))^-1 = ((x-13)/3)^(1/3)

If x = -11 then ((-11-13)/3)^(1/3) = -8^(1/3) = -2
0 like 0 dislike
0 like 0 dislike
You have to pass the function G(x) as the parameter of f(x) so therefore, foreach x in the f(x) expression you calculate G(x)...

No related questions found

24.8k questions

103k answers

0 comments

33.7k users

OhhAskMe is a math solving hub where high school and university students ask and answer loads of math questions, discuss the latest in math, and share their knowledge. It’s 100% free!